Facile growth of centimeter-order, highly crystalline ZnWO4 single crystals by the flux evaporation technique using molten NaCl. Issue 44 (19th October 2016) - Yamada, Tetsuya; Sukegawa, Yuta; Wagata, Hajime; Yubuta, Kunio; Teshima, Katsuya
Abstract : Centimeter-order, idiomorphic ZnWO4 crystals were facilely grown from molten NaCl as a flux, while undefined particles were obtained by a solid-state reaction. Abstract : Wolframite-type ZnWO4 crystals were grown from molten NaCl using the flux method at temperatures between 700 and 1100 °C. Centimeter-order, idiomorphic single crystals of ZnWO4 were easily obtained from a solute concentration of 40 mol% at 1100 °C, with well-defined facets at 010, 101, −101, 130, and 041. As the heating temperature decreases, the size of the ZnWO4 crystals also decreases. However, millimeter-order ZnWO4 single crystals were still grown from a NaCl flux at 700 °C, whereas solid-state reactions gave only indefinite, micron-order particles even at 1100 °C. It is assumed that NaCl and ZnWO4 form a eutectic composition, resulting in effective crystal growth through a liquid-phase process even below the melting point of NaCl (∼800 °C). In addition, the large-scale evaporation of molten NaCl should facilitate the supersaturation of ZnWO4 crystals, resulting in centimeter-order growth at 1100 °C. The crystallographic characteristics of the flux-grown ZnWO4 crystals were also evaluated; elemental analysis and microscopic observations revealed a highly crystalline nature with respect to chemical stoichiometry, impurities, crystal defects, and regularity of the lattice.